2007
DOI: 10.1002/ejoc.200700153
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiomerically Pure cis‐ and trans‐4‐Amino‐1‐oxyl‐2,2,6,6‐tetramethylpiperidine‐3‐carboxylic Acid: A Spin‐Labelled, Cyclic, Chiral β‐Amino Acid, and 3D‐Structural Analysis of a Doubly Spin‐Labelled β‐Hexapeptide

Abstract: Amination of 3‐carboxymethyl‐1‐oxyl‐2,2,6,6‐tetramethyl‐4‐piperidone (1) with either (R)‐ or (S)‐α‐methylbenzylamine gave corresponding enamines 2. Whereas the reduction with NaBH3CN/CH3COOH afforded predominantly a mixture of two possible cis diastereomers of 3, (1′R,3S,4S)/(1′R,3R,4R) or (1′S,3R,4R)/(1′S,3S,4S), which could be separated by crystallisation of their HCl salts, the use of NaBH4/(CH3)2CHCOOH as the reducing agent resulted in a mixture of one trans‐ and one cis diastereomer of 3 (1′R,3S,4R)/(1′R,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Recently, DeGrado and co‐workers29 showed that the amide I′ spectrum of a helical β‐peptide in D 2 O is quite complex because it is characterised by three bands centred at $\tilde \nu $ =1612, 1624, and 1650 cm −1 . Finally, our ACHC/β‐TOAC model hexapeptide mentioned above12 shows a main band at $\tilde \nu $ =1654 cm −1 accompanied by weak shoulders at $\tilde \nu $ =1624 and 1682 cm −1 in CDCl 3 . All of these β‐peptides are folded in the 14‐helix structure.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Recently, DeGrado and co‐workers29 showed that the amide I′ spectrum of a helical β‐peptide in D 2 O is quite complex because it is characterised by three bands centred at $\tilde \nu $ =1612, 1624, and 1650 cm −1 . Finally, our ACHC/β‐TOAC model hexapeptide mentioned above12 shows a main band at $\tilde \nu $ =1654 cm −1 accompanied by weak shoulders at $\tilde \nu $ =1624 and 1682 cm −1 in CDCl 3 . All of these β‐peptides are folded in the 14‐helix structure.…”
Section: Resultsmentioning
confidence: 73%
“…[4][5][6][7] We have explored the extension of this approach to bpeptide foldamers. [11] A model b-hexapeptide, containing two (3R,4S)-b-TOAC residues [12] combined with four (1S,2S)-2-aminocyclohexane carboxylic acid (ACHC) residues (Scheme 1), was synthesised and the preferred conformation (i.e., 3 14 -helix) [1,2] was assessed in particular by continuous-wave (cw) EPR spectroscopic analysis. [12] Herein, we have expanded this area by utilising the enantiopure five-membered ring (3R,4R)-4-amino-1-oxyl-2,2,5,5-tetramethylpyrrolidine-3-carboxylic acid (POAC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β‐TOAC was designed as a spin label with reduced mobility, as required for the investigation of β‐peptide structures in solution . Nevertheless, similar to the α‐TOAC the β‐analogue, is likely to influence the natural secondary structure formation . Therefore, we report the synthesis of the conformationally semi‐rigid 4‐(3,3,5,5‐tetramethyl‐2,6‐dioxo‐4‐oxylpiperazin‐1‐yl)‐ d ‐β 3 ‐homophenylglycine (β 3 ‐hTOPP) spin label for β‐peptides.…”
Section: Methodsmentioning
confidence: 99%
“…Balog et al, 2003; M. R. Balog et al, 2004; Kalai, Schindler, Balog, Fogassy, & Hideg, 2008; Tominaga et al, 2001; Wright et al, 2007). The most commonly used one is 2,2,6,6-tetramethyl-N-oxyl-4-amino-4-carboxylic acid (TOAC, Figure 1, 8 ) (Rassat & Rey, 1967; Schreier, Bozelli, Marín, Vieira, & Nakaie, 2012; A.…”
Section: Peptide Labeling With Epr Active Probes and Preparation Omentioning
confidence: 99%